Computer-oriented mathematical physics - Greenspan, Donald (International series in nonlinear mathematics ;, 1981)
Computer-Oriented Mathematical Physics describes some mathematical models of classical physical phenomena, particularly the mechanics of particles. This book is composed of 12 chapters, and begins with an introduction to the link between mathematics and physics. The subsequent chapters deal with the concept of gravity, the theoretical foundations f classical physics as a mathematical science, and the principles of pendulum and other oscillators. These topics are followed by discussions of waves, vectors, gravitation, the body-problem, and discrete fluid models. The final chapters examine the.